Dynamic analysis of offshore wind turbine blades under the action of wind shear and fluctuating wind - Jianping Zhang (Journal of Vibroengineering, 2018)
Aiming at large-scale offshore wind turbine blades, governing equations in fluid domain and motion equations in structural domain with geometric nonlinearity were built by the aid of ALE method. A three dimensional model under fluid-structure interaction (FSI) was established by using UG software and Geometry module, and numerical calculation for FSI vibration characteristics of wind turbine blades under the effects of wind shear and fluctuating wind was carried out based on ANSYS Workbench. The results indicate that the contribution of the combined action to displacement and Mises stress chiefly derives from the wind shear effect, which not only causes a comparatively larger increase for the maximum displacement and Mises stress, but also becomes bigger and bigger with the increase of average wind speed, and the fluctuating wind effect is insignificant. The maximum value of Mises stress in the blade section appears at the relative wingspan of 0.55, the maximum Mises stress varying with relative span length decreases progressively from the middle to both sides of the blade, and the contribution of wind shear effect alone, the combined action or wind speed increment to stress also shows the same change rule. Furthermore, in the maximum stress section along wingspan, Mises stress along the direction of blade thickness or chord length respectively presents two distribution laws, and reaches the maximum on the blade surface.